(untitled) (Jurnal Pustaka, 2026)
This study aims 1) To determine the process of developing animated video media in history learning in class XI 1 SMAN 1 Sentajo Raya. 2) To determine the feasibility of animated video media in history learning in class XI 1 SMAN 1 Sentajo Raya. 3) To determine the effectiveness of animated video media in increasing interest in learning history in class XI 1 SMAN 1 Sentajo Raya. This study uses the type of R&D (Research and Development) research with the ADDIE development model. Based on the results of the study, validation from material experts obtained a percentage of 90% and validation from media experts obtained a percentage of 92%, both of which are categorized as very feasible. Meanwhile, the assessment of student responses for small groups obtained a percentage of 88% and large groups obtained a percentage of 92%, both of which are categorized as very feasible. In measuring student learning interest in class XI 1, it was found that there was an increase before and after the use of animated video media, namely: 1) Feelings of pleasure 55.55% to 85.55%; 2) Attention 57.77% to 87.03%; 3) Interest increased from 57.03% to 88.88%; 4) Student involvement increased from 60.37% to 83.70%. Therefore, it can be concluded that animated video media is suitable for use in the history learning process and is able to increase students’ interest in learning history.